Uji Aktivitas Antibakteri Ekstrak Daun Karenda (Carissa carandas Linn.) Terhadap Bakteri Propionibacterium acne dan Staphylococcus epidermidis - Vera Estefania Kaban; Nasri Nasri; Hariyadi Dharmawan Syahputra; Muhammad Fauzan Lubis; Denny Satria (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Karenda leaves contain flavonoids, steroids or triterpenoids, saponins, and tannins that act as antimicrobial compounds. The aim of the study was to determine the antibacterial activity of the ethanol extract of Karenda leaves against several acne-causing bacteria. The research method involved characterizing the simplicia of karenda leaves and extract preparation by maceration using 96% ethanol as a solvent. and test the antibacterial activity of the ethanol extract of Karenda leaves using the agar diffusion method. The bacteria used were Propionibacterium acnes and Staphylococcus epidermis. The extract concentrations used were 300, 150, 125, 100, 75, 50, 25, and 5 mg/mL. Based on tests carried out by the ethanol extract of karenda leaves, the diameters of the inhibition zones were 7.2 ± 0.12 respectively; 7.8±0.10; 9.7±0.15; 11.23±0.25; 12.43±0.06; 13.57±0.06; 14.20±0.10; 16.47 ± 0.21 for Propionibacterium acne and 8.17 ± 0.06; 9.37 ± 0.15; 9.80 ± 0.10; 10.73 ± 0.15; 11.27±0.12; 12.43±0.06; 13.77±0.06; 15.47 ± 0.12 for Staphylococcus epidermis. he test results proved that 300 mg/mL was the best concentration for inhibiting the growth of Propionibacterium acnes and Staphylococcus epidermis bacteria.